Painful pictures of the epigastrium and left hypochondrium: It treatment for denervation or pancreatic resections - Valls, Alberto; Sarroca, Carlos (Cirugía del Uruguay, 1979)
The paper discusses the problem of chronic painful syndrome of epigastrium not accounted far by lesions of biliary tract and gastroduodenum and which do not respond to medical treatment. In surgical exploration, the need to investigate the retrocavity of epiplons is underined, by reason of the frequency of pancreatic lesions. Surgical solution consists mainly in pancreatic resection as well as in pancreatic denervation, specially in Napalkov's peripheral neurotomy.